The Romantic poets and Post-War Serbian poetry - Šeatović-Dimitrijević, Svetlana (Wydawnictwo Rys (nr 1), 2011)
The pathetic or melancholy tone of Serbian Romanticism was quite unacceptable for modern poets who preferred irony, oxymoron, contrast, and a disharmonic world image. In the poetry of Stevan Raičković and Desanka Maksimović, connected by certain poetic affinities, we find a distinct lyrical overtone and an orientation towards a simple, mythopoeic world image, inspired by the heritage of Serbian Romanticism. In Serbian Romanticism, poetry had a populist role and that sort of function did not quite correspond to the functions of post-war poetry. After the war, poetry was marked by a struggle for poetic freedom or cautious efforts on the social and political level in poetry of Vasko Popa, Ivan V. Lalic and Ljubomir Simovic. Contemporary poetry did not relinquish that task, but its poetic language is more nuanced, more delicate, freed from the vocabulary and the rhetoric of oral poetry, as well as from its pathetic-melancholy tone.
Keywords: Serbian modern poetry; Serbian Romanticism; Poetic language; Literary tradition; Neoromanticism